3A+6(A+2)=

Simple and best practice solution for 3A+6(A+2)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3A+6(A+2)= equation:


Simplifying
3A + 6(A + 2) = 0

Reorder the terms:
3A + 6(2 + A) = 0
3A + (2 * 6 + A * 6) = 0
3A + (12 + 6A) = 0

Reorder the terms:
12 + 3A + 6A = 0

Combine like terms: 3A + 6A = 9A
12 + 9A = 0

Solving
12 + 9A = 0

Solving for variable 'A'.

Move all terms containing A to the left, all other terms to the right.

Add '-12' to each side of the equation.
12 + -12 + 9A = 0 + -12

Combine like terms: 12 + -12 = 0
0 + 9A = 0 + -12
9A = 0 + -12

Combine like terms: 0 + -12 = -12
9A = -12

Divide each side by '9'.
A = -1.333333333

Simplifying
A = -1.333333333

See similar equations:

| 3(6x-1)-4(2x-16)=3(3x+3)-4 | | T=-16t^2+Vt+s | | 3r^2-2r=-5 | | 7x(x+6)=6 | | 3r^2-2r+5=0 | | y^4-y^2+2=0 | | 4x-8x+6=18 | | 15p^2+4p-49=0 | | 7p^2-38-24=0 | | 3x-4(1-x)+18=24 | | k=3y-15+2y | | 171=14x+3 | | x+63+2x=180 | | -171=14x+3 | | 10x^2-26=-12 | | 2y+14+4y-6=90 | | (2+z)(4z-9)=0 | | X/4=×/5-14 | | 7i*8i= | | 2y+14+4y-6=180 | | 3G+6(g+2)= | | 14=12y+7x | | 3(x-5)=-2-7x | | 10=8y+9x | | y+1=sqrt-y+19 | | 7(0)+15y=-21 | | 0=-8t^2+20t+10 | | x+2.5x=500 | | 6x-2+4x+6+x=180 | | 2x=6y-42 | | 3(2-x)+7x=-12 | | 5-4a-8=7+a |

Equations solver categories